Usage of biological chitosan against the contamination of post-harvest treatment of strawberries by Aspergillus niger - El-araby, Abir; El Ghadraoui, Lahsen; Errachidi, Faouzi (Frontiers in Sustainable Food Systems, 2022)
Developing bioactive food packaging, capable of extending the shelf life of fruits, has received increasing attention in recent years. The present study highlights the interest in post-harvest treatment for strawberries with chitosan as a preservation solution. Chitosan extraction was carried out from shrimp shells (Parapenaeus longirostris), composed of chitin, using citric acid during the demineralization step. Extracted chitosan was characterized by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and scanning electron microscopy (SEM). The presence of amino group (-NH2) in the obtained chitosan was confirmed by infrared (IR) spectral data. Deacetylation degree (DD), which has a value of 80.86%, was determined by FTIR spectra. X-ray diffraction pattern (XRD) showed two peaks of crystalline character, characteristic of extracted chitosan, approximately at 20° and 30° (2θ). Extracted chitosan morphology was studied by scanning electron microscopy (SEM) and showed a relatively smooth top surface and fibrous structures. Chitosan, acetic acid, and their interaction effects were evaluated on Aspergillus niger mycelial growth strain isolated from spoiled strawberries. Chitosan revealed a strong anti-fungal activity, dose-dependent (from 0 to 3%), on Aspergillus niger mycelial growth, while acetic acid showed moderate anti-fungal activity against the Aspergillus niger strain. Agri-food application was carried out using chitosan solubilized in acetic acid as a post-harvest treatment tool for the prolongation of shelf life of strawberries (by using an experimental design). Coating, with the developed preservative solution, significantly reduced microbial spoilage in strawberries. Treated strawberries retained their initial pigmentation for a longer period when compared to untreated strawberries. The treatment carried out maintained the cellular structures of treated strawberries during the storage period and thus extended the shelf life of strawberries which is considered very susceptible to reduce post-harvest losses.